Dark romanticism in Chris Grey’s popular songs: from obsession to the new life process - Saragih, Evi Irawanti Br; Wirawan, Muh. Firsa; Mutmainnah, Mutmainnah; D, Ayu Triria P. (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Dark Romanticism on literature is a subgenre of the Romantic movement that emerged in the early 19th century. This genre emphasizes the darker dimensions and negative aspects of the human condition. In this day, works within the Dark Romanticism genre are no longer confined to literary forms such as novels, short stories, or poetry, but also extended into the music industry particularly through songs that explore tragic love, toxic relationships, and emotional suffering. The growing interest in songs that embrace the themes of Dark Romanticism in music markets indicates a strong emotional resonance between such works and the internal experiences of their listeners. One artist who consistently engages with Dark Romantic themes in his music is Chris Grey, a Jamaican-descended musician. The lyrics in his songs frequently portray emotional dependency on a love object, despair following rejection, and a life consumed by illusions, often manifesting as obsession. According to Carl Gustav Jung, obsession is a manifestation of the unconscious shadow—the part of the self that contains repressed or hidden aspects deemed incompatible with one’s ideal self-image. Obsession arises when an individual fails to detach from the object at the centre of their emotional fixation. This study aims to examine the stages of obsession as represented in the lyrics of Chris Grey’s songs, and to trace the transition toward a renewed sense of hope following the Dark Romantic (obsessive) phase. It is hoped that this research contributes to interdisciplinary discourse particularly in understanding the emotional dynamics present in popular culture.